(3efgd GdZeGe aj TQM TQGFY GdESdGes - (3YHGS Hf MSf Hf LYaQ cGTa GdZWGA, J (B1323(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdhcGdI aJMG hcSQG GSe ef GdJhcjd TQYg HGdVQhQj hGdSfI GdeJhGJQI bjd hHGdcJGH HMcGjI CUMGH Gdcgas
(3BNQgG (B:s
(3BNQgG(B: (3heQ aj Gdhba JaUjdg(B. (3GdKGdKI UObI GdSQ CaVd ef UObI GdLgQ(B. (3hGQaY GdMHC GdbGHV hGHYOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B23: 125s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis